NanoPhotonic structures for biosensing applications - Emam, Ahmed Bassam (AUC Knowledge Fountain, 2018)
Photonics -“ science of optics“ - has become one of the emerging sciences in many applications nowadays. The study of light interaction with matter has opened a lot of interesting phenomena that differ in their applications including sensing, modulation, demultiplexing, etc. Sensing applications represent a major part in the photonics field owing to their crucial role in the detecting and diagnosis of diseases in many medical applications. On the other hand, gas sensing is considered an important application in many industrial centers. During the manufacturing of several products, toxic gases may be generated and hence the ability to detect such types of gases becomes a necessity. The first part of this thesis is concerned with sensing applications using plasmonic and photonic structures. Several plasmonic and photonic structures are proposed that are characterized by their ultimate sensitivity and high performance. Other parameters are taken into consideration like the CMOS compatibility of our design and the possibility of being integrated with electronic chips. Beside optical sensing and their important role in biomedical and environmental applications, optical demultiplexers are considered from the main blocks in different communication systems that are based on wavelength division multiplexing (WDM). The need to highly select certain wavelength to carry the data during transmission is increasing. In the second part of the thesis, the design methodology of an optical filter is discussed. The optical filter can fit into many applications including demultiplexing and sensing. An optical demultiplexer is proposed and characterized by its high selectivity of wavelength in the near-infrared range to fit with the telecommunication systems. In addition, the transmission levels are of an acceptable range to ensure high signal to noise ratio. 9 The third and the last part of the thesis is concerned with optical coupling from free-space to guided structures. In the last part, an optical grating coupler is proposed that is characterized by its high transmission levels. The grating coupler couples the light from free-space to a shallow waveguide with a narrow lateral dimension. Such system can fit in many applications including sensing and modulation applications.